2020
DOI: 10.1371/journal.pone.0226516
|View full text |Cite
|
Sign up to set email alerts
|

Population-based estimates of humoral autoimmunity from the U.S. National Health and Nutrition Examination Surveys, 1960–2014

Abstract: ObjectiveBased on US National Health and Nutrition Examination Survey (NHANES) data, we attempted to provide an unbiased, population-based estimate of autoantibody prevalence overall and by age and sex. MethodsUS autoantibody prevalence estimates for detectable rheumatoid factor, anti-thyroglobulin, anti-thyroperoxidase, anti-transglutaminase, anti-endomysial, anti-GAD65, antinuclear autoantibodies, and autoantibodies to extractable nuclear antigens were estimated from the 1960-1962 National Health Examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 76 publications
0
10
1
Order By: Relevance
“…The US population is aging and increased autoantibody and autoimmune disease prevalence is reported. 39 Because participants were older adults, the results might not generalize to autoimmune diseases that primarily have their onset in younger people. However, the pathogenesis of many of the specific autoimmune diseases observed (eg, rheumatoid arthritis and psoriasis) is similar in younger adults.…”
Section: Discussionmentioning
confidence: 99%
“…The US population is aging and increased autoantibody and autoimmune disease prevalence is reported. 39 Because participants were older adults, the results might not generalize to autoimmune diseases that primarily have their onset in younger people. However, the pathogenesis of many of the specific autoimmune diseases observed (eg, rheumatoid arthritis and psoriasis) is similar in younger adults.…”
Section: Discussionmentioning
confidence: 99%
“…The National Health and Nutrition Examination Survey (NHANES), which collects detailed data on diet, nutritional status, and chronic disease to inform nutrition and health policy, is the cornerstone for national nutrition monitoring in the US (29). The objectives of the current study were to present an analysis using this large, cross-sectional, nationallyrepresentative database to assess the intake status of v antioxidant micronutrients with a known role in CVD, and explore the effects of combined exposure to these antioxidants on CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we hypothesize that women have an evolutionarily conserved tendency toward enhanced B‐cell activation and production of higher levels of antibodies, which results in increased incidence of antibody‐driven autoimmune diseases. This hypothesis stems from our observation that women have more serum immunoglobulins (i.e., antibodies) than men at baseline (Butterworth et al., 1967; Crisp & Quinn, 2009; Dillon et al., 2020; Rowley & Mackay, 1969) and in response to challenges like infection or vaccination (Cook, 2008; Rowley & Mackay, 1969). While this difference may peak in the first two decades of life (Oyeyinka et al., 1984), women seem to have more absolute antibody levels than men lifelong (Crisp & Quinn, 2009; Dillon et al., 2020).…”
mentioning
confidence: 99%
“…This hypothesis stems from our observation that women have more serum immunoglobulins (i.e., antibodies) than men at baseline (Butterworth et al., 1967; Crisp & Quinn, 2009; Dillon et al., 2020; Rowley & Mackay, 1969) and in response to challenges like infection or vaccination (Cook, 2008; Rowley & Mackay, 1969). While this difference may peak in the first two decades of life (Oyeyinka et al., 1984), women seem to have more absolute antibody levels than men lifelong (Crisp & Quinn, 2009; Dillon et al., 2020). A recent study showed that women have not only more antibodies in general, but also autoantibodies (Dillon et al., 2020).…”
mentioning
confidence: 99%